1992
DOI: 10.1007/bf01400612
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative spondylodiscitis: Results of a prospective study about the aetiology of spondylodiscitis after operation for lumbar disc herniation

Abstract: In 412 patients undergoing surgery for herniated lumbar discs from September 1986 to September 1987 and from January 1988 to July 1989 a microbiological specimen was taken from the intervertebral disc space and from the cover of the operating microscope. Also the tips of the wound drains were examined microbiologically after removal. 17% of the patients had a positive bacteriological culture from their intervertebral disc space; 12% of the specimen from the operating microscope were positive. These results fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 17 publications
1
40
1
4
Order By: Relevance
“…The incidence of late spondylodiscitis was 0.26% (N = 1) after a mean follow-up of 10 months and a follow-up rate of 95.5% (N = 382). Different mechanisms and/or aetiologies of early and late spondylodiscitis will not be discussed here and are described in detail elsewhere [6,9,11,26,29].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of late spondylodiscitis was 0.26% (N = 1) after a mean follow-up of 10 months and a follow-up rate of 95.5% (N = 382). Different mechanisms and/or aetiologies of early and late spondylodiscitis will not be discussed here and are described in detail elsewhere [6,9,11,26,29].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal biopsy for bacteriologic diagnosis has a variable rate of reported success in patients with spondylitis [4,12,13]. Tronnier et al [1] reported bacterial growth from the intervertebral disc space, tips of wound drains, and operating microscope specimens in a high percentage of cases although infections occurred in only 0.2 % of these cases. The specific microorganism, which causes the vast majority of disc space infections during open or percutaneous procedures, is Staphylococcus aureus [1,2,4].…”
Section: Introductionmentioning
confidence: 98%
“…Intervertebral discitis most frequently occurs following spinal surgery, such as myelography, lumbar puncture, paravertebral injection, and percutaneous discectomy, for the procedures that afford entry for bacteria into the susceptible disc space [1][2][3][4][5][6][7]. Perioperative contamination by various microorganisms is considered to be the main etiologic factor in postoperative spondylodiscitis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A incidência varia de 0,2% a 15% 24,26 . Em casos de artrodese e de instrumentação cirúrgica, a taxa de infecção pode chegar até a 8% 9 , e a 10,3% nas reoperações 21 .…”
Section: Introductionunclassified
“…O risco de infecção pós-operatória é maior em pacientes idosos, diabéticos, desnutridos, em uso prolongado de glicocorticóides, em longas hospitalizações, que se submeteram à radioterapia, com antecedente de neoplasia e naqueles com disrafismos espinhais 21,26 .…”
Section: Introductionunclassified